CORRIGENDUM FOR 10.1210/en.2012-2130 (Endocrinology, 2016)
CONTEXT: Thyroid dysfunction and menopause both affect cardiovascular risk, but the specific influence of the menopausal transition on thyroid function independent of aging remains unclear. OBJECTIVE: To examine longitudinal changes in thyroid function across the menopausal transition among a large cohort of healthy midlife women. DESIGN: Longitudinal cohort study (2004-2024) using annual health checkup data and interrupted time-series analyses within mixed-effects linear models. SETTING: Annual health screening program at St. Luke's International Hospital, Tokyo, Japan. PARTICIPANTS: 7,644 Japanese women who experienced natural menopause and had at least one health checkup both before and after menopause. Those with hormone therapy or surgical menopause were excluded. MAIN OUTCOME MEASURES: Serum TSH and free thyroxine (fT4) levels. Secondary outcomes included abnormal TSH categories (>4.5, >10.0, <0.4, and <0.1 mIU/L) and self-reported thyroid disorders. RESULTS: Over a median 13.7-year follow-up (86,967 visits), TSH increased by 0.014 mIU/L per year (95% CI, 0.010 to 0.019) before menopause, with no significant slope change at menopause (additional change, -0.006 mIU/L per year [CI, -0.012 to 0.000]). fT4 levels decreased by 0.005 ng/dL per year (CI, -0.006 to -0.005) before menopause and stabilized thereafter (additional slope change, +0.005 ng/dL per year [CI, 0.004 to 0.005]). The prevalence of abnormal TSH and thyroid disorders increased with age, but there were no distinct changes at menopause. CONCLUSIONS: Menopause was not associated with clinically meaningful changes in thyroid function beyond aging. Age-related factors, rather than the menopausal transition, may largely explain increasing thyroid abnormalities in midlife women.